Development of a Questionnaire to Measure Impact and Outcomes of Brachial Plexus Injury. (7th February 2018) - Mancuso, Carol A.; Lee, Steve K.; Saltzman, Eliana B.; Model, Zina; Landers, Zoe A.; Dy, Christopher J.; Wolfe, Scott W.
Abstract : Background: The physical and psychological impact of brachial plexus injury (BPI) has not been comprehensively measured with BPI-specific scales. Our objective was to develop and test a patient-derived questionnaire to measure the impact and outcomes of BPI. Methods: We developed a questionnaire in 3 phases with preoperative and postoperative patients. Phase 1 included interviews of patients using open-ended questions addressing the impact of BPI and improvement expected (preoperative patients) or received (postoperative patients). Phase 2 involved assembling a draft questionnaire and administering the questionnaire twice to establish test-retest reliability. Phase 3 involved selecting final items, developing a scoring system, and assessing validity. Patient scores using the questionnaire were assessed in comparison with scores of the Disabilities of the Arm, Shoulder and Hand (DASH) and RAND-36 measures. Results: Patients with partial or complete plexopathy participated. In Phase 1 (23 patients), discrete categories were discerned from open-ended responses and became items for the preoperative and postoperative versions of the questionnaire. In Phase 2 (50 patients [14 from Phase 1]), test-retest reliability was established, with weighted kappa values of ≥0.50 for all items. In Phase 3, 43 items were retained and grouped into 4 subscales: symptoms, limitations, emotion, and improvement expected (preoperative) or improvement received (postoperative). A score for each subscale, ranging from 0 to 100, can be calculated, with higher scores indicating more symptoms, limitations, and emotional distress, and greater improvement expected (or received). Preoperative scores were worse than postoperative scores for the symptoms, limitations, and emotion subscales (composite score of 48 compared with 38; p = 0.05), and more improvement was expected than was received (69 compared with 53; p = 0.01). Correlations with the DASH (0.44 to 0.74) and RAND-36 (0.23 to 0.80) for related scales were consistent and moderate, indicating that the new questionnaire is valid and distinct. Conclusions: We developed a patient-derived questionnaire that measures the physical and psychological impact of BPI on preoperative and postoperative patients and the amount of improvement expected or received from surgery. This BPI-specific questionnaire enhances the comprehensive assessment of this population.